Replantation of an Amputated Hand at Wrist Level Due to Self-Mutilation: Considerations in Management - Vardharajan, Ashwini; Mohan, Monusha; Pushpanathan, Dakshana; Venkatramani, Hari; Sabapathy, S. Raja (Indian Journal of Plastic Surgery, 2023)
Major self-mutilations include injury to limbs, eyes, or genitals due to various psychiatric illnesses. Limb amputations are grievous injuries that radically decrease the quality of life. Controversy exists as to the advisability of replantation of the self-amputated limb. We report a case of self-amputation of the hand in a 54-year-old gentleman in a fit of psychosis. He underwent replantation of the hand and was given timely psychiatric help. Interdisciplinary management helped in improving the mood of the patient and he cooperated well with the rehabilitation schedule. Recent literature encourages surgeons to replant the limb and treat the mental illness with close observation for warning signs. We conclude that replantation along with early initiation of psychiatry treatment can help the patient overcome psychosis, realize the implications of his actions, and provide the motivation to perform physiotherapy to achieve the optimum outcome possible in the replanted hand.
Keywords: major self-mutilation; replantation; psychiatry